Baseline characterization of aquaculture systems in Kwara State Nigeria - Lozano, Denise; Manyise, Timothy (WorldFish, 2022)
Presentation from the Training in the application of characterization surveys and use of CAPI for enumerators in Kwara, Nigeria.